Geodatabase development for forest restoration and biodiversity conservation in the Mt. Makiling Forest Reserve, Philippines - Bantayan, Nathaniel C.; Abraham, Emmanuel Rodantes G.; Fernando, Edwino S. (2008)
A GIS-based database (or geodatabase) was developed for the Mt. Makiling Forest Reserve, on LuzonIsland, Philippines toward the establishment of a management decision support system. The studypresents initial results in the development of a geodatabase, as well as the use of geographic informa-tion system (GIS) in the planning, design and implementation of programs for forest renewal andbiodiversity conservation. GIS use for data encoding is already extensive but its use as a planning andanalytical tool is limited, if not altogether lacking. An outline for the establishment of a geodatabase ispresented that will allow processing, analysis and modeling and, ultimately, the sustainable develop-ment and conservation of the mountain forest reserve, which is a significant watershed area and animportant catchment for Laguna de Bay - the largest freshwater lake in Southeast Asia. The database design is patterned after the GAME model earlier developed. GAME is an acronym forGIS-based assessment, monitoring and evaluation which uses regular-shaped polygons to provide afull description of the watershed. There are five (5) levels of detail or precision that can be used tocharacterize and map watershed phenomena: 100-ha grids, 25-ha quadrants, 1-ha cells, 0.04-ha squaresand 0.01-ha granules. Depending on the level of detail required for analysis, the appropriate precisionlevel can be used to describe land use/land cover, especially degraded areas, habitats, species distri-butions and conservation hotspots, among others. The geodatabase for the Mt. Makiling Forest Re-serve already contains data and information on soils, slope, elevation and land use. © Published by the College of Agriculture.
Keywords: Mount Makiling Forest Reserve; Geographic Information Systems